Yield and quality of sweet corn at different plant populations - Souza, Renan Soares de; Vidigal Filho, Pedro Soares; Scapim, Carlos Alberto; Marques, Odair José; Queiroz, Dyane Coelho; Okumura, Ricardo Shigueru; José, Jefferson Vieira; Reche, Deivid Lincoln; Cortinove, Vinícius Bovo (Semina: Ciências Agrárias, 2013)
The objective of this study was to evaluate the plant population density effect upon yield components and the chemical composition of grains in two sweet corn hybrids in "Winter-Spring" cultivation. The experimental design used was the complete randomized blocks with four replications. The treatments were based on the combination between two sweet corn hybrids (Tropical Plus e RB-6324) and five plant populations (40,000, 55.000, 70,000, 85,000 and 100,000 plants ha-1), in a factorial scheme 2 x 5, evaluated in two "winter-spring" growing seasons (2009 and 2010). The increment in the population of 40,000 to 100,000 plants ha-1 resulted in higher husked commercial corn ear productivity in both hybrids, Tropical Plus and RB-6324. The increase of plant population reduced the length and diameter of corn ears in Tropical Plus and RB-6324. The mass of the corn ears from Tropical Plus also reduced; however, it did not affect the commercial standard and industrial use. In larger plant populations the hybrid RB-6324 produced corn ears with grains that were sweeter and with lower starch content. The hybrid Tropical Plus presented higher mass, length, productivity, sugar content and lower diameter of corn ears when compared to RB-6324.